2014
DOI: 10.1016/j.sbspro.2014.09.219
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Trait Anxiety Levels of Physical Education and Sports Students (Ibrahim Cecen University Case)

Abstract: This study aims to analyze the trait anxiety levels of physical education and sports students and to compare them in terms of certain variables (gender, doing sports regularly and being a registered athlete). The research population is composed of students studying in the School of Physical Education and Sports, Agri Ibrahim Cecen University; while the sample group consists of 209 students studying in the Departments of Physical Education and Sports Teaching (n=147) and Coaching Education (n=62). "State-Trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…23 Covid-19'un yayılım hızını azaltmak amacıyla izolasyon uygulanan dönemlerde bireylerde ağırlıklı olarak olumsuz duygusal durumlar gözlemlenmekte 24 v e bu doğrultuda benzeri psikolojik problemlerin yaşanma ihtimalleri artmaktadır. 25 Her ne kadar sportif faaliyetlerin psikolojik beceriler [26][27][28][29] ve yaşam becerileri [30][31][32] üzerinde etkili olduğu bilinse de sporcuların da bu olumsuz koşullardan etkilenmesi söz konusudur. Belirtilen koşullarda kişilerarası iletişim yokluğu neticesinde depresyon ve kaygının ortaya çıkması ya da kötüleşmesi olasıdır.…”
Section: Introductionunclassified
“…23 Covid-19'un yayılım hızını azaltmak amacıyla izolasyon uygulanan dönemlerde bireylerde ağırlıklı olarak olumsuz duygusal durumlar gözlemlenmekte 24 v e bu doğrultuda benzeri psikolojik problemlerin yaşanma ihtimalleri artmaktadır. 25 Her ne kadar sportif faaliyetlerin psikolojik beceriler [26][27][28][29] ve yaşam becerileri [30][31][32] üzerinde etkili olduğu bilinse de sporcuların da bu olumsuz koşullardan etkilenmesi söz konusudur. Belirtilen koşullarda kişilerarası iletişim yokluğu neticesinde depresyon ve kaygının ortaya çıkması ya da kötüleşmesi olasıdır.…”
Section: Introductionunclassified
“…The present study has found that athletes with higher hope emphasize the best way to face challenges in adversity. When faced with obstacles or frustrations, they only focus on finding breakthroughs and rarely focus on making excuses for failure (Kuczka and Treasure, 2005;Martinent and Ferrand, 2007;Kaya et al, 2014;Chen and Chi, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of sports anxiety, some studies have found that female athletes have significantly higher sports competition anxiety than males ( Chen and Chi, 2009 ; Rasquinha et al, 2014 ); individual sports athletes have higher precompetition anxiety than team sports athletes ( Grossbard et al, 2007 ) while elite athletes in team sports have higher precompetition anxiety than elite athletes in individual sports. Athletes with 1 year of sports experience have significantly more precompetition anxiety than those with 6 years of sports experience, and young athletes formally selected into the team have lower precompetition state anxiety than the substitute athletes ( Zeidner, 1991 ) while successful athletes have less precompetition state anxiety than less successful athletes ( Martinent and Ferrand, 2007 ; Kaya et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many assumptions that in order to achieve the best performance for sports people must be able to eliminate perceived anxiety. Though anxiety is a basic human feeling since their existence on earth [6], it cannot be eliminated but can be controlled [7]. Controlling anxiety during a sports situation will make performance more optimal, because actually anxiety can have a positive effect, only at certain limits and after that anxiety can negatively affect the athlete's achievement [8].…”
Section: Introductionmentioning
confidence: 99%